Chez Panisse : building an open innovation ecosystem - Chesbrough, Henry William, (SAGE Knowledge. Cases., 2017)
The Chez Panisse case study provides a brief history of the famous restaurant started by Alice Waters, but in the context of open innovation and the ecosystem that Waters developed over 40 years. The case study discusses Waters local and global ecosystem using an open innovation strategy with stakeholders such as suppliers, alumni chef and staff, food writers, and others. Over the years, Chez Panisse became a launching pad for numerous prominent chefs, suppliers, and food writers, along with the well-known Edible School Yard Project (ESY) that helped fund edible schoolyards across the country. All of these members flowed in and out of Chez Panisse and became part of the restaurants greater ecosystem, a factor that enabled and spurred numerous collaborations and innovations over the years.As Waters looked back at Chez Panisses 43-year-old history, she was very proud of all she and her team and extended ecosystem had accomplished. Going forward, she wondered how to continue the success of the restaurant and the wide-reaching global ecosystem she had built and hoped to continue to grow, as well as how to continue to spread her philosophy that the best-tasting food is organically and locally grown and harvested in ways that are ecologically sound by people who are taking care of the land for future generations.